Peran Guru dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Buddha Kelas IX di SMP Metta Maitreya Pekanbaru - Natalia Wahyuni; Rida Jelita; Eko Wahyono Tikno (STAB Maitreyawira, 2023)
This study is entitled “Teacher’s role to improve student’s learning passion in Buddhist Religion Grade IX at SMP Metta Maitreya Pekanbaru. This study is held at SMP Metta Maitreya Pekanbaru to discuss about the teacher’s role as informator, educator, and motivator in improving learning passion for grade IX students in SMP Metta Maitreya Pekanbaru. There are problem identification from this study which are how the teacher’s role as motivator to improve the learning passion and what the supporting and obstacle factors of the teacher as a motivator to improve the learning passion. The goal of this study is to acknowledge the teacher’s role as motivator to improve the learning passion and to discover the support and obstacle factors of the teacher’s role to improve the learning passion in Buddhist religion for the grade IX students of SMP Metta Maitreya Pekanbaru. This study uses descriptive analysis methods with qualitative approach. The technical of data collection is to observe the interview and documentation. The result that could be seen as the study is : 1) to use various techniques in teaching, 2) to make competition, 3) to evaluate, 4) to scoring, 5) to announce the result of lesson, 6) to give the reward, 7) to praise the students, 8) to punish the ones who don’t do the task. Meanwhile the supporting factors are students’ health, the seriousness will of learning from the students, teacher’s competence and qualification. The obstacle factors are lacking in giving appreciation to students, the low understanding of topics by the students, and also the less availability of the school facility.